The sedimentation of memory. Issue 5 (4th July 2018) - Sharr, Adam
Abstract : This paper explores how architecture can embody the past. In the context of Berlin—the site of much prominent contemporary memorial architecture—it examines one project in detail: Reitermann and Sassenroth's widely overlooked Chapel of Reconciliation, completed in 2000. This building, I argue, demonstrates a distinctive and critically acute approach to memory. Unlike the Memorial to the Murdered Jews of Europe, designed by Peter Eisenmann, and the Jewish Museum, designed by Daniel Libeskind, which are projects that make worlds-unto-themselves—and unlike the work of Carlo Scarpa in Verona, or Sverre Fehn at Hamar, or Peter Zumthor in Cologne, where layers of history are conspicuously displayed one-on-top-of-the-next—the Chapel displays a sedimentary approach to the past. This sedimentation is not an outright rejection of history; nor does it suggest that history proceeds as a single, linear narrative. While the Chapel's architecture may not have immediate visceral impact, its thoughtfulness and subtlety repay careful scrutiny. The chapel is read here as a cultural artefact, its organisation and details examined in relation to its specific historical, physical and intellectual contexts.